Institutional Governance for the Utilization of Post Replanting Sustainable Palm Oil in Riau Province - Mayarni; Zaili Rusli; Geovani Meiwanda; Abdul Sadad (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
Built-in oil palm plantations have multiple functions, namely economic, social and environmental functions that are not owned by other sectors outside agriculture. With this multifunctionality, oil palm plantations contribute, both economically, socially and environmentally, to the achievement of the SDGs. This study aims to determine institutional governance related to utilizing palm sap into brown sugar as a source of post-replanting income in order to improve the sustainable economic aspects of the community. This research chooses a descriptive research with a qualitative approach. The results of this study found that in the management of palm sap in the village of maredan barat, tualang sub-district, siak district, during the replanting period, a strong and well-coordinated management system was needed, so that the management of this palm sap could develop, especially to improve the community's economic level in a sustainable manner, considering the potential of palm oil which is still in nature. global and has a long-term advantage. Increasing partnerships in terms of management is also a major aspect for the realization of this sustainability.